Effect of co-culture of mesenchymal stem/stromal cells with pancreatic islets on viability and function outcomes: a systematic review and meta-analysis. Issue 2 (4th March 2017) - de Souza, Bianca Marmontel; Bouças, Ana Paula; Oliveira, Fernanda dos Santos de; Reis, Karina Pires; Ziegelmann, Patrícia; Bauer, Andrea Carla; Crispim, Daisy
ABSTRACT: The maintenance of viable and functional pancreatic islets is crucial for successful islet transplantation from brain-dead donors. To overcome islet quality loss during culture, some studies have co-cultured islets with mesenchymal stem/stromal cells (MSC). However, it is still uncertain if MSC-secreted factors are enough to improve islet quality or if a physical contact between MSCs and islets is needed. Therefore, we performed a systematic review and meta-analysis to clarify the effect of different culture contact systems of islets with MSCs on viability and insulin secretion outcomes. Pubmed and Embase were searched. Twenty studies fulfilled the eligibility criteria and were included in the qualitative synthesis and/or meta-analysis. For both outcomes, pooled weighted mean differences (WMD) between islet cultured alone (control group) and the co-culture condition were calculated. Viability mean was higher in islets co-cultured with MSCs compared with islet cultured alone [WMD = 18.08 (95% CI 12.59–23.57)]. The improvement in viability was higher in islets co-cultured in indirect or mixed contact with MSCs than in direct physical contact (P <0.001). Moreover, the mean of insulin stimulation index (ISI) was higher in islets from co-culture condition compared with islet cultured alone [WMD = 0.83 (95% CI 0.54–1.13)], independently of contact system. Results from the studies that were analyzed only qualitatively are in accordance with meta-analysis data. Co-culture of islets with MSCs has the potential for protecting islets from injury during culture period. Moreover, culture time appears to influence the beneficial effect of different methods of co-culture on viability and function of islets.